2018
DOI: 10.1002/cncr.31395
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in postmastectomy breast reconstruction: National trends in utilization from 2005 to 2014

Abstract: The use of postmastectomy breast reconstruction is steadily rising in the United States. Racial disparities persist, but progress has been made. Further efforts are needed to reduce racial disparities. Cancer 2018;124:2774-2784. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 45 publications
4
57
0
Order By: Relevance
“…5 Using the American College of Surgeons National Surgical Quality Improvement Program database, Epstein et al reported that the use of postmastectomy reconstruction was significantly lower for AI/AN women compared with NHW women. 6 In addition to diagnostic and treatment disparities, breast cancer diagnosed among AI/AN women also may be more inherently aggressive. Using the SEER database, Chen and Li reported that the risk of triple-negative breast cancer was significantly increased among AI/AN women compared with NHW women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5 Using the American College of Surgeons National Surgical Quality Improvement Program database, Epstein et al reported that the use of postmastectomy reconstruction was significantly lower for AI/AN women compared with NHW women. 6 In addition to diagnostic and treatment disparities, breast cancer diagnosed among AI/AN women also may be more inherently aggressive. Using the SEER database, Chen and Li reported that the risk of triple-negative breast cancer was significantly increased among AI/AN women compared with NHW women.…”
Section: Discussionmentioning
confidence: 99%
“…Javid et al reported that the use of surveillance after breast cancer treatment was significantly reduced in AI/AN women compared with NHW women 5 . Using the American College of Surgeons National Surgical Quality Improvement Program database, Epstein et al reported that the use of postmastectomy reconstruction was significantly lower for AI/AN women compared with NHW women 6 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in public health policy may be correlated with recent measured reductions in breast reconstruction disparities. 3,4 In contrast to breast reconstruction, investigation into disparities within facial plastic and reconstructive surgery literature has been limited, including examination of rhinoplasty outcomes. Patient-reported outcomes (PROMs) are increasingly seen as significant to assessing treatment success in facial aesthetic and reconstructive surgery, including rhinoplasty.…”
mentioning
confidence: 99%